2003
DOI: 10.1149/1.1536181
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Organic Contamination Behavior on Silicon Wafer Surface

Abstract: This study theoretically and experimentally evaluates the role of the coexisting organic compounds on the time-dependent airborne organic contamination on a silicon wafer surface in the cleanroom air. The maximum contamination and the ratio of the desorption to the adsorption are independently described from each other, using simple equations consisting only of the surface concentrations of the organic compounds on the silicon wafer surface. These parameters are consistent with the experiment using the silicon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 17 publications
0
39
1
Order By: Relevance
“…[14][15][16][17] This model consists of first-order rates of adsorption and desorption as expressed in the following equation:…”
Section: Deposition Kinetics Of Dep and Dbp On Sio 2 Wafersmentioning
confidence: 99%
See 2 more Smart Citations
“…[14][15][16][17] This model consists of first-order rates of adsorption and desorption as expressed in the following equation:…”
Section: Deposition Kinetics Of Dep and Dbp On Sio 2 Wafersmentioning
confidence: 99%
“…8 In a number of recent studies, the deposition kinetics of several phthalate compounds on silicon wafers have been reported for long exposure periods up to several days. [13][14][15][16] However, in actual semiconductor fabrication processes, the wafer exposure time is most frequently limited to only a few hours. Nonetheless, it is possible that, even at a short exposure time, the wafer surface density of oAMCs with relatively lower molecular weight (M W ) could exceed the threshold contamination levels to result in device deterioration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contamination is due to volatile organic compounds in laboratory air and in wafer storage containers, as well as to a surface hydration layer. 7,8 Past experience indicated that the contamination level would be on the order of 0.3 nm and would likely be the largest source of error in the ellipsometric thickness determinations unless physically eliminated or measured by another technique and subtracted from the total ellipsometric thickness of oxide plus contamination. Because of the time lapse between wafer fabrication at NC State University and measurement at NIST and SEMATECH, it was necessary to deal directly with the contamination.…”
Section: Ellipsometry Measurement and Analysismentioning
confidence: 99%
“…Particularly, the influence of gas velocity should be clarified, because not only the QCM sensor, but also the wafers are usually exposed to air at the position having various air velocities depending on the arrangement of the wafers and the equipment (15,16,25,26). Therefore, the adsorption and desorption of water and diethyl phthalate (DEP), widely known contaminant (3,5) on silicon surface, are studied in detail using the quartz crystal microbalance method in ambient nitrogen having wide ranges of humidity, average gas velocity and DEP concentration, in addition to our previous studies (22,23).…”
Section: Introductionmentioning
confidence: 99%